2020
DOI: 10.1152/ajpheart.00559.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke extract induces ferroptosis in vascular smooth muscle cells

Abstract: Cigarette smoking is a major risk factor for aortic aneurysm and dissection; however, no causative link between smoking and these aortic disorders has been proven. In the present study, we investigated the mechanism by which cigarette smoke affects vascular wall cells and found that cigarette smoke extract (CSE) induced a novel form of regulated cell death termed ferroptosis in vascular smooth muscle cells (VSMCs). CSE markedly induced cell death in A7r5 cells and primary rat VSMCs, but not in endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(86 citation statements)
references
References 43 publications
2
82
0
2
Order By: Relevance
“…Although NCOA4-mediated ferritinophagy has been implicated in chronic obstructive pulmonary disease, stroke, and ischemia-reperfusion injuries 21 , the molecular mechanisms modulating ferritinophagy and ferroptosis remain obscure. The cigarette smoke induced ferroptosis in bronchial epithelial cells 19,27 and vascular smooth muscle cells 28 , and NCOA4-mediated ferritinophagy promoted ROS accumulation in epithelial cells 27 . Continuous severe cold stress-induced ferroptosisis relied on the apoptosis signal-regulating kinase 1 (ASK1)-p38 MAPK activation 20 , which is also involved in Erastin-induced ferroptosis 29 .…”
Section: Discussionmentioning
confidence: 97%
“…Although NCOA4-mediated ferritinophagy has been implicated in chronic obstructive pulmonary disease, stroke, and ischemia-reperfusion injuries 21 , the molecular mechanisms modulating ferritinophagy and ferroptosis remain obscure. The cigarette smoke induced ferroptosis in bronchial epithelial cells 19,27 and vascular smooth muscle cells 28 , and NCOA4-mediated ferritinophagy promoted ROS accumulation in epithelial cells 27 . Continuous severe cold stress-induced ferroptosisis relied on the apoptosis signal-regulating kinase 1 (ASK1)-p38 MAPK activation 20 , which is also involved in Erastin-induced ferroptosis 29 .…”
Section: Discussionmentioning
confidence: 97%
“…Degradation of ferritin releases large quantities of free iron into the labile iron pool, which can trigger excessive intracellular ROS, exhaust pool of cytosolic glutathione, and promote lipid peroxidation 5 . Previously, activation of ferritinophagy has been correlated with cell death of cancer cells, 20,29 and such ferritinophagy‐induced cell death participated in cigarette smoke‐induced chronic obstructive pulmonary diseases, 30‐32 urinary tract infections, 5 and sepsis‐induced cardiac injury 33 . Recent studies showed that ferritinophagy may also play physiological roles in the erythropoiesis in the bone marrow when mice were in iron deficiency, and NCOA4‐knockout mice display microcytosis and mild anemia 8,34 …”
Section: Discussionmentioning
confidence: 99%
“…It necessitates the entrance into the cell of the Fe +++ /transferrin complex via the transferrin receptor and its reduction in Fe ++ by endosomal ferric reductase at pH 5.2-5.6. It was recently shown that smoking-induced SMC toxicity in the CV system is mediated by ferroptosis [56]. Therefore, both SMCs and endothelial cells could be targets for ferroptosis [57].…”
Section: Early Stages Of Atheromamentioning
confidence: 99%